Fugindo do quintal: empreendedores e incubadoras de empresas de base tecnológica no Brasil - Furtado, Marco Antônio Tourinho (1995)
This study presents a research made in seven technology based business incubators, in cities as Brasília, Campina Grande, Florianópolis, Rio de Janeiro and São Carlos (Brazil). It has used interviews with structured questions that reffer to the beginning, the difficulties and the advantages that entrepreneurs and their companies have been undergoing in technology based business incubators in Brazil, It also reffers to the structure, supports, weaknesses and strongs points of these incubators.